Application of Molecular Dynamic Simulation in the Enantiorecognition Mechanism of the Pharmaceutically Relevant Leu-Phe Dipeptides With Four Zwitterionic Chiral Stationary Phases - Varfaj, Ina; Sardella, Roccaldo; Klimova, Yana A; Asnin, Leonid D; Kohout, Michael; Carotti, Andrea (Journal of separation science, 2025)
In order to broaden the applicability of the molecular dynamics technique and to further validate the efficacy of a computational protocol recently developed in our laboratory, the present study aims to elucidate the enantiorecognition mechanisms involving four zwitterionic Cinchona alkaloid-based CSPs under reversed-phase (RP) conditions. In this study, we use the enantiomeric dipeptides D-leucine-D-phenylalanine and L-leucine-L-phenylalanine as probes to investigate the properties of CHIRALPAK ZWIX(+) and ZWIX(-), as well as ZWIX(+A) and ZWIX (-A). The Leu-Phe dipeptide has considerable potential in the pharmaceutical field due to its potential applications in drug delivery, therapeutics and as a building block for peptidomimetics. Furthermore, Leu-Phe is one of the few uncapped dipeptides composed of natural amino acids capable of forming stable hydrogels. The in silico protocol was successfully optimized by setting the simulation box size, run time, and number of frames to record to generate molecular dynamics trajectories as informative as possible. Importantly, the analyses were in complete agreement with the experimental EO, providing insights into the driving forces involved in the enantiorecognition mechanism. In particular, salt bridges and hydrogen bonds were confirmed as the primary interactions, while π-π and π-cation interactions were identified as complementary to facilitate the SO-SA association.
Keywords: Molecular Dynamics Simulation; molecular dynamic simulations; dipeptidy; simulace molekulární dynamiky; fenylalanin; Dipeptides; HPLC; zwitterionic Cinchona alkaloids‐based chiral stationary phases; enantiorecognition mechanism; Stereoisomerism; stereoizomerie; Phenylalanine